Perancangan Ulang Tata Letak Fasilitas untuk Meningkatkan Produktivitas dan Efisiensi Biaya Menggunakan Metode Systematic Layout Planning - Suseno, Novie Susanti; Aulawi, Hilmi; Rustandi, Rustandi (Institut Teknologi Garut, 2024)
In today's modern era, industrial development is increasingly rapid. This further encourages the development of businesses in all fields. One of them is the convection industry. The emergence of more new companies resulted in increasingly fierce competition. To win this competition, companies must use various strategies. Problems in layout result in overstock and high handling costs. Therefore, layout plays an important role in increasing space use efficiency, reducing handling costs and increasing process capacity. This research aims to design a facility layout that can increase productivity and cost efficiency in CV. Zahra Sewing House. The method used in layout design is the SLP (Systematic Layout Planning) method with the help of BLOCPLAN software. Based on the analysis of the Activity Relationship Chart (ARC), an alternative layout proposal was produced using the SLP method and BLOCPLAN software. Based on the results and data processing that has been carried out, there is a decrease in OMH (Material Handling Costs) in both proposals